2020
DOI: 10.1128/aem.00133-20
|View full text |Cite
|
Sign up to set email alerts
|

Fumonisin and Beauvericin Chemotypes and Genotypes of the Sister Species Fusarium subglutinans and Fusarium temperatum

Abstract: Fusarium subglutinans and Fusarium temperatum are common maize pathogens that produce mycotoxins and cause plant disease. The ability of these species to produce beauvericin and fumonisin mycotoxins is not settled, as reports of toxin production are not concordant. Our objective was to clarify this situation by determining both the chemotypes and genotypes for strains from both species. We analyzed 25 strains from Argentina, 13 F. subglutinans and 12 F. temperatum strains, for toxin production by ultraperforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
0
11
0
Order By: Relevance
“…In their previous assessment in Peru, Logrieco and colleagues found the strains of F. subglutinans they isolated to primarily produce beauvericin and moniliformin, two mycotoxins qualified as “emerging”, i.e., mycotoxins that are “neither routinely determined, nor legislatively regulated” with, however, “the evidence of their incidence is rapidly increasing” [ 43 ]. In line with these results, in Argentina, F. temperatum was also detected as a frequent contaminant of maize kernels but isolated strains largely produced beauvericin and only a few of them produced Fumonisins [ 44 , 45 ]. Consistent monitoring across several years would be required considering that Peru is subjected to extreme climatic events, notably El Niño/La Niña events, that are prime factors for contaminations with mycotoxins [ 46 ].…”
Section: Discussionmentioning
confidence: 65%
“…In their previous assessment in Peru, Logrieco and colleagues found the strains of F. subglutinans they isolated to primarily produce beauvericin and moniliformin, two mycotoxins qualified as “emerging”, i.e., mycotoxins that are “neither routinely determined, nor legislatively regulated” with, however, “the evidence of their incidence is rapidly increasing” [ 43 ]. In line with these results, in Argentina, F. temperatum was also detected as a frequent contaminant of maize kernels but isolated strains largely produced beauvericin and only a few of them produced Fumonisins [ 44 , 45 ]. Consistent monitoring across several years would be required considering that Peru is subjected to extreme climatic events, notably El Niño/La Niña events, that are prime factors for contaminations with mycotoxins [ 46 ].…”
Section: Discussionmentioning
confidence: 65%
“…FB1 and FB2 were also detected in one culture of F. subglutinans. Even though F. subglutinans was occasionally reported to produce fumonisins [ 63 ], which is a common feature among members of the FFSC, both classical [ 18 ] as well as modern studies [ 64 , 65 , 66 , 67 ] convincingly showed that F. subglutinans does not produce fumonisins. Mycotoxin production found in a small set of cultures of F. verticillioides and F. proliferatum confirmed the established mycotoxin spectra of these species [ 59 , 68 , 69 , 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the FFSC, the ability of fumonisin production is correlated with the presence of FUM genes but not correlated with phylogenetic relationships [59,87]. Lack of FUM genes was indicated in the species that had been reported as fumonisin producer (F. napiforme, F. dlamni, F. subglutinans, F. temperatum) [67,77,89,90]. The possible reason for these irrationals is an intraspecific variation of fumonisin producibility.…”
Section: Overviewmentioning
confidence: 98%
“…Wang et al [75] reported that F. temperatum from maize in China produced fumonisin under field conditions and Fumero et al [76] detected fumonisin production in 25% of F. temperatum strains from maize in Argentina. Recently, Fumero et al [77] obtained the whole genome sequence of a F. subglutinans strain and a F. temperatum strain from Argentina and that suggested absence of FUM genes and fumonisin production in these strains.…”
Section: Fusarium Temperatummentioning
confidence: 99%